2011
DOI: 10.1007/s00535-011-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

Impedance-pH reflux patterns can differentiate non-erosive reflux disease from functional heartburn patients

Abstract: In patients with normal AET and SAP+, increased number of weakly acidic reflux and higher rate of proximal reflux are the main discriminant features. There is large overlap between FH and HVs. These differences can be of help in diagnosing patients with normal oesophageal acid exposure who fail to have symptoms during MII-pH testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 46 publications
5
61
1
5
Order By: Relevance
“…20 Accordingly, we found the following 3 results. First, FH/PPI-responders had similar AET, total reflux number, acid reflux number, proximal reflux number, as well as similar baseline impedance values and PSPW index to HE.…”
Section: Discussionmentioning
confidence: 77%
“…20 Accordingly, we found the following 3 results. First, FH/PPI-responders had similar AET, total reflux number, acid reflux number, proximal reflux number, as well as similar baseline impedance values and PSPW index to HE.…”
Section: Discussionmentioning
confidence: 77%
“…It has been revealed that 37%-60% of NERD patients have normal acid reflux, and the proportion of FH and RH can vary from less than 10% to 75% and to 36%, respectively. [14][15][16][17][18][19][20][21][22][23][24][25] One factor that has contributed to the variation is the changing definitions of heartburn phenotypes. For example, the Rome III committee used to define those with normal reflux but positive symptom-reflux association as NERD, but these patients were then isolated as a single group named RH in the updated criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies, using pH-impedance monitoring evaluated the prevalence of reflux hypersensitivity. Savarino et al 7 assessed 329 endoscopy negative patients with a pH-impedance monitoring off PPI treatment. The authors demonstrated that 40% of the patients had NERD, 24% functional heartburn, and 36% reflux hypersensitivity.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have produced conflicting results regarding the role of non-acidic reflux or proximal esophageal migration of gastroesophageal reflux in reflux hypersensitivity. Savarino et al 7 demonstrated that an increased number of weakly acidic reflux events and a high rate of proximal reflux are the main causes of symptoms in reflux hypersensitivity patients who were evaluated with multichannel impedance (MII)-pH monitoring. In contrast, Tamura et al 16 reported that the total and proximal acid reflux events were significantly higher in NERD patients with abnormal esophageal acid exposure as compared with reflux hypersensitivity patients.…”
Section: Pathophysiologymentioning
confidence: 99%